TEACHER LEADERSHIP IN THE CLASS ON STUDENT CHARACTER BUILDING (Case Study at SMK Pelayaran Samudera Indonesia – Medan) - Titim Eliawati; Dina Irmayanti Harahap (Journal MELT (Medium for English Language Teaching), 2018)
This study aims to get answers as a result of an in-depth analysis of the role of teacher leadership in the classroom in the formation of student characters. The focus of this research is the formation of student character and sub focus is the role of teacher leadership. This research was conducted at SMK Pelayaran Samudera Indonesia - Medan by using qualitative approach and research method was case study. This study was conducted based on data obtained from the grand tour results and the results of some previous research on teacher leadership and its relevance to the formation of character education students. The result of this research was teacher leadership is very influential on student character formation.